Implementation Of Integrated Quality Management In Media-Based Chemistry Learning Information And Communication Technology As Graduates - Arin Tentrem Mawati; Iim Wasliman; Hanafiah; Rita Sulastini (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This research is motivated by the low implementation of ICT-based chemistry learning, schools have not been able to implement ICT-based chemistry learning in achieving graduate quality. The purpose of this study was to determine the implementation of integrated quality management of ICT-based chemistry learning as an effort to improve the quality of graduates. This research is a qualitative research with case study method. Data collection techniques used are observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data is by triangulation of sources and techniques. Regulation of the minister of education and culture Number 20 of 2016 concerning competency standards for elementary and secondary education graduates, regarding the meaning, purpose, and scope of SKL as well as Monitoring and Evaluation. Definition of Graduate Competency Standards are criteria regarding the qualifications of graduates' abilities which include attitudes, knowledge, and skills. The results of research at SMAN 1 Bandung City and SMA Al Azhar Syifa Budi Parahyangan West Bandung in general indicate that the implementation of integrated quality management of ICT-based chemistry learning in both schools has been going well so that it can improve the quality of graduates.